2014
DOI: 10.1261/rna.036343.112
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of 6S RNA release-defective mutants uncovers features of pRNA-dependent release from RNA polymerase in E. coli

Abstract: 6S RNA is a noncoding RNA that inhibits bacterial transcription by sequestering RNA polymerase holoenzyme (Eσ 70 ) in lownutrient conditions. This transcriptional block can be relieved by the synthesis of a short product RNA (pRNA) using the 6S RNA as a template. Here, we selected a range of 6S RNA release-defective mutants from a high diversity in vitro pool. Studying the release-defective variant R9-33 uncovered complex interactions between three regions of the 6S RNA. As expected, mutating the transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In one study it was found that cells expressing a mutant 6S RNA were delayed in restarting growth, suggesting pRNA-synthesis mediated release of Eσ 70 from Ec 6S RNA is required for efficient restart of growth after stationary phase (35). Toxic effects of expressing this type of mutant RNA also were observed, although the extent of toxicity was dependent on expression levels (35, 79). However, the non-releasing 6S RNA mutant regulated transcription similarly to wild type 6S RNA in stationary phase, both in specificity of promoters sensitive and insensitive to 6S RNA and the extent of regulation (35).…”
Section: S Rna – a Template For Prna Synthesismentioning
confidence: 97%
See 2 more Smart Citations
“…In one study it was found that cells expressing a mutant 6S RNA were delayed in restarting growth, suggesting pRNA-synthesis mediated release of Eσ 70 from Ec 6S RNA is required for efficient restart of growth after stationary phase (35). Toxic effects of expressing this type of mutant RNA also were observed, although the extent of toxicity was dependent on expression levels (35, 79). However, the non-releasing 6S RNA mutant regulated transcription similarly to wild type 6S RNA in stationary phase, both in specificity of promoters sensitive and insensitive to 6S RNA and the extent of regulation (35).…”
Section: S Rna – a Template For Prna Synthesismentioning
confidence: 97%
“…Detection of pRNA synthesis in vitro provided strong evidence for the similarity of Ec 6S RNA and open complex DNA interactions with Eσ 70 . However, it was the determination that pRNA synthesis occurs in vivo, along with subsequent work, that demonstrated that pRNA synthesis is one mechanism to regulate Ec 6S RNA by contributing to the off-rate of 6S RNA from RNA polymerase (35, 64, 78, 79). For bacteria beyond E. coli and B. subtilis , the specific role of pRNA synthesis has not been investigated directly, but pRNAs have been detected in vivo for additional bacterial species (e.g.…”
Section: S Rna – a Template For Prna Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The 6S RDM plasmid was created as previously described (Dolgosheina et al 2014) but with point mutations corresponding to the R9-33 construct (Oviedo Ovando et al 2014). The 6S RDM is flanked by a T7 promoter and lac operator at its 5 ′ end and an intrinsic terminator at its 3 ′ end and was cloned into the pEcoli-Cterm-6xHN (Clontech) plasmid between the SgrAI and ClaI sites.…”
Section: Construction Of the P6srdm_t7 Plasmidmentioning
confidence: 99%
“…Insertion of a single Mango tag into stem-loop VII of the S. cerevisiae (yeast) U1 small nuclear RNA (snRNA) maintained yeast viability and enabled the single step pull-down of the U1 snRNP using TO1-Dtb under native conditions. Tagging a release-defective form of the bacterial 6S RNA (Oviedo Ovando et al 2014) with Mango (6S RDM ) allowed the purification of the 6S RDM :RNA polymerase complex in two steps: the second of which involved the use of TO1-Dtb fluorescence to track RNP elution. Using Mango-tagged 6S RNA, eGFP-tagged RNA polymerase, and TO3-Dtb, we could track the binding and release of the 6S RNA from the RNP (Wassarman and Storz 2000;Wassarman and Saecker 2006;Panchapakesan and Unrau 2012) by an electrophoretic mobility shift assay (EMSA).…”
Section: Introductionmentioning
confidence: 99%